726 Relationships Between Sleep and Psychological Adjustment During the COVID-19 Pandemic. (3rd May 2021) - Gilles, Allyson; Qeadan, Fares; Baron, Kelly
Abstract: Introduction: Disruption of daily routines (employment, social interaction, health behaviors) during the COVID-19 pandemic has contributed to psychological distress (worry, rumination), likely impacting sleep-related behaviors. This study evaluated change in psychological adjustment and insomnia symptoms during the COVID-19 pandemic. Methods: The sample included 192 adults from Utah who completed three data collection cycles across 9 consecutive months to assess self-reported depressive, anxiety, and insomnia symptoms. Anxiety and depressive symptoms were assessed via the Generalized Anxiety Disorder scale (GAD-7) and Patient Health Questionnaire depression scale (PHQ-8). Insomnia was measured by the Insomnia Severity Index (ISI). Data were analyzed using mixed-effect modeling and adjusted for anxiety and depression to determine their independent effects on insomnia symptoms. Spaghetti plots examined mean changes over time and significance was set at p<0.05. Average anxiety, depression, and insomnia severity scores were aggregated for each month. Results: As participants' symptoms of anxiety and depression increased in severity, insomnia symptoms increased similarly. Over half of participants reported clinically significant ISI scores (59.38%). In both the random intercept and random slope models, there were significant independent effects of anxiety on insomnia severity (F=20.69; p<0.0001) and significant effects of depression on insomnia severity (F=87.44, p<0.0001). While the change in insomnia severity over time was on the boundary of statistical significance (F=3.54; p=0.0618), dropping from 15.17 (April) to 12.58 (December), our longitudinal analyses revealed no significant difference for the effect of anxiety or depression in predicting insomnia severity over time. Participants' monthly averages varied for sleep and psychological scores (ISI) from 12.58 to 16.07 (SD=3.76 to 6.34 for December and September, respectively), (GAD-7) from 3.47 to 6.39 (SD=3.36 to 5.26 for December and June, respectively), and (PHQ-8) 4.47 to 6.10 (SD=4.65 to 4.39 for December and June, respectively). Conclusion: Results demonstrate high prevalence of insomnia symptoms during the COVID-19 pandemic and underscore the importance of examining mental health functioning and psychological resiliency on sleep in order to enhance prevention efforts in response to a significant stressor. Support (if any):